2000
DOI: 10.1002/1097-4636(200011)52:2<285::aid-jbm7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Studies on nerve cell affinity of chitosan-derived materials

Abstract: Reparation of the central nervous system (CNS) is important because when it is impaired its recovery is difficult and concomitant malfunction of other parts of body occurs. In our previous studies, chitosan was found to be a good material supporting nerve repair. The purpose of this article was to study the ability of chitosan and some chitosan-derived materials to facilitate the growth of nerve cells. Those materials were chitosan, glutaraldehyde-crosslinked chitosan, glutaraldehyde-crosslinked chitosan-gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…It was already reported that besides its good biocompatibility, chitosan has an excellent nerve cell affinity. Extracellular molecules such as laminin, fibronectin, and other serum proteins have a good affinity to chitosan [20]. Although there were some differences in the cellular adhesion and proliferation rate ARTICLE IN PRESS Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was already reported that besides its good biocompatibility, chitosan has an excellent nerve cell affinity. Extracellular molecules such as laminin, fibronectin, and other serum proteins have a good affinity to chitosan [20]. Although there were some differences in the cellular adhesion and proliferation rate ARTICLE IN PRESS Fig.…”
Section: Discussionmentioning
confidence: 99%
“…22 Haipeng et al reported that neurons cultured on the chitosan membrane grew well and that chitosan tube promote repair of the peripheral nervous system. 23 Yuan et al found that chitosan fibers supported the adhesion, migration, and proliferation of Schwann cells, which provide a similar guide for regenerating axons to Büngner bands in the nervous system. 24 However, to the best of our knowledge, no report has been appeared yet on chitosan-based scaffolds for the differentiation of hADSC into neuron-like cells (hADSC-NLCs).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a biodegradable, inexpensive material with low toxicity that can be modified through incorporation of ECM proteins to the surface, including laminin and fibronectin that regulate cell functions (Haipeng et al, 2000;Cheng et al, 2007;Yang et al, 2010). Accordingly, due to its ability to be modified, chitosan carriers have demonstrated NSC survival, proliferation, and cell differentiation into desired phenotypes (Yang et al, 2010).…”
Section: Chitosanmentioning
confidence: 99%